Culture and Tourism: Valuing and Preserving the Historical and Artistic Memory of the Historical Center of Lima World Heritage Site - Moscoso Zelaya, Gladys (2019)
The world undergoes accelerated changes, globalization emerges in a decisive way, which is why there is an urgent need to talk about culture and tourism, the main tools that will allow the development of the city; it is possible with the entrance of visitors who arrive motivated and who are attracted in searching new cultural experiences .Tourism is an activity that is promoted with greater interest. Some years ago, qualifying language emerged describing Lima as “Lima, the ugly”, “Lima the chaotic” and “Lima the slum” but our city has been transformed into a “Beautiful Lima”, a place of great appeal in the last 15 years. Mayors nowadays have discovered the historical and artistic wealth that it possesses, having more than 600 monuments that are located in the Historical Center of Lima and Rimac, declared by Unesco in the year 1991 as World Heritage. This article aims to raise awareness of the importance to preserve and value the monuments that host this important tourist axis.